Analisis Briket Biomassa Campuran Bagasse dan Kulit Tebu terhadap Performa Kompor Gasifikasi (TLUD) - Aron Enruico (Fakultas Teknik, 2024)
Introduction: The population growth in Indonesia from 270 million in 2020 to 279 million in 2024 has led to increased consumption of LPG, potentially causing future fuel shortages. The Top Lit Up Draft (TLUD) gasification stove offers a solution by enhancing thermal efficiency and producing minimal smoke using abundant biomass, such as sugarcane bagasse. This biomass can be processed into charcoal briquettes with high calorific value and low emissions. Purpose: This study aims to produce and test biomass briquettes made from a mixture of bagasse and sugarcane peel for use in the TLUD gasification stove as an alternative fuel. These types of biomass are processed into charcoal briquettes with high calorific value and low emissions. Methods: This experimental laboratory research involves testing the calorific value of raw bagasse and sugarcane peel before carbonization, as well as briquette mixtures (70:30, 50:50, 30:70) using a bomb calorimeter. The fuel briquettes are tested by operating the TLUD stove, both with boiling water to 90°C (water boiling test) and without boiling water. Data collected include flame duration, combustion chamber temperature, flame height, water temperature rise, char weight, and boiling time. Results: The study shows that the 30:70 bagasse-tosugarcane peel briquette composition has the highest calorific value of 6242.292 cal/gram, followed by the 70:30 composition at 6094.753 cal/gram and the 50:50 composition at 5657.935 cal/gram. The 30:70 composition also exhibited the longest flame duration (119 minutes 32 seconds), highest flame temperature (570.2°C), and greatest flame height (11.468 cm). The TLUD stove efficiency with the water boiling test reached 56.41%, with a char weight of 61 grams and a water temperature rise from 28.4°C to 90.4°C in 10 minutes 45 seconds. Conclusion: Briquettes made from a mixture of bagasse and sugarcane peel with a higher proportion of sugarcane peel have a high calorific value and better quality for use as fuel.
Entry oleh Arif 2026 Maret 16
Keywords: Briquettes mixture of bagasse and sugarcane peel; Gasification stove TLUD; Calorific value